The Correlation between the Covid-19 Pandemic and Domestic Abuse Against Women: A Comparative Study Between Australia, Indonesia, and India - Jessica Ruth Andina; Marvel Tanara; Dzaky Putra Wirahman (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2020)
The onset of the Covid-19 global pandemic in early 2020 forced many governments to quarantine their citizens within their own homes over the course of the year - namely from the early to middle months of the year. This was then followed by a surge of domestic violence cases against women, most often by their own spouses. This problem seemed to be a global problem as it affected any countries regardless of how high or low they score in the Gender Development Index. This paper attempts to discuss the factors behind such a phenomenon and scrutinise what it represents through the lenses of gender theories. The paper will also analyse the studied countries’ governments’ approach to this issue. To that end, three countries from three different levels of GDI rankings are studied: Australia (ranked high), Indonesia (ranked medium) and India (ranked low). A brief explanation regarding this non-endemic issue will also be drawn from each countries’ individual variables.